Evaluation of mutagenicity associated with Escherichia coli inactivation in UV-treated orange juice. Issue 2 (7th February 2017) - Rodríguez, Maria; Oteiza, Juan; Giannuzzi, Leda; Zaritzky, Noemi
ABSTRACT: UV radiation is an alternative technology for the elimination of pathogenic micro-organisms in liquid food. The objectives of this work were to investigate mutagenesis using the Ames test in : (1) fresh squeezed orange juice submitted to UV radiation doses required to achieve 5 and 10 log10 reductions of different strains of Escherichia coli serotype O157:H7 at two temperatures, and (2) commercial pasteurized orange juice submitted to thermal treatment. Two histidine-auxotrophic strains, Salmonella Typhimurium TA98 and TA97a, were used in the Ames test with and without metabolic activation. In commercial pasteurized orange juices, mutagenesis was not observed with S. Typhimurium TA98 strain with and without metabolic activation, but high mutagenic effect was observed using TA97a with metabolic activation. UV radiation did not affect the stability of ascorbic acid in aqueous solution. However, degradation of ascorbic acid was observed when UV treatment was performed on squeezed orange juice, following first order kinetics. UV treatment required to achieve 5 log10 reductions (1.5 J/cm 2 ) did not show a mutagenic effect with and without metabolic activation using the tested strains, but a higher UV radiation dose necessary to produce 10 log10 reductions (3.0 J/cm 2 ) showed mutagenicity with metabolic activation.